2020
DOI: 10.1103/physrevb.101.020413
|View full text |Cite
|
Sign up to set email alerts
|

Far- and midinfrared excitation of large amplitude spin precession in the ferromagnetic semiconductor InMnAs

Abstract: Ultrafast laser excitation of the ferromagnetic semiconductor InMnAs is shown to trigger spin precession with the largest amplitude reported for magnetic semiconductors so far. To reveal the electronic transitions mediating the coupling between light and spins, we compared the spin dynamics triggered by short teraherz-(photon energy 5 meV) and mid-infrared (photon energy 500 meV) pulses. The experiments reveal that THz pump pulses excite qualitatively similar spin dynamics, but 100 times more energy efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This trend is consistent with the data reported in Ref. 11, where for the pump at the wavelength of 2500 nm (photon energy: 0.5 eV), no saturation was observed for pump fluences up to 30 mJ/cm 2 .…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This trend is consistent with the data reported in Ref. 11, where for the pump at the wavelength of 2500 nm (photon energy: 0.5 eV), no saturation was observed for pump fluences up to 30 mJ/cm 2 .…”
supporting
confidence: 93%
“…[4][5][6][7][8] It was discovered that femtosecond excitation of free carriers, i.e., intraband electronic transitions, in magnetic metals is able to launch ultrafast demagnetization on a subpicosecond timescale 9 and even to reverse magnetization without any magnetic fields. 10 In our recent paper, 11 we have studied spin dynamics induced in ferromagnetic semiconductor InMnAs by terahertz (THz) and infrared (IR) pulses, which triggered intraband and interband electronic transitions, respectively. The experiments revealed that THz and IR pump pulses induce ultrafast demagnetization at nearly similar timescales, but THz pulse does it 100 times more energy efficiently than the IR counterpart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An external magnetic field H ≈ 1.5 kOe along the sample normal was applied to force the magnetization to get aligned out of plane. Detailed descriptions of the THz setup have been reported elsewhere [29,30].…”
Section: Resultsmentioning
confidence: 99%